Pengaruh Asimetri Informasi, Profitabilitas, dan Ukuran Perusahaan Terhadap Manajemen Laba Riil: Penelitian pada Perusahaan Manufaktur di Bidang Tekstil yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Noviar Usman Varisi; Yuli Tri Cahyono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The aim of this research is to test and analyze the influence of information asymmetry, profitability and company size on real earnings management. Hypothesis testing was carried out with a sample of 60 manufacturing companies in the textile sector listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The sampling method uses purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The research results show that information asymmetry and company size have an effect on real earnings management, while profitability has no effect.